15.34% efficiency all-small-molecule organic solar cells with an improved fill factor enabled by a fullerene additive - Hu, Dingqin; Yang, Qianguang; Chen, Haiyan; Wobben, Friso; Le Corre, Vincent Marc; Singh, Ranbir; Liu, Tao; Ma, Ruijie; Tang, Hua; Koster, L Jan Anton; Duan, Tainan; Yan, He; et al. (Energy and Environmental Science, 2020)
Solution processed organic solar cells (OSCs) composed of all small molecules (ASM) are promising for production on an industrial scale owing to the properties of small molecules, such as well-defined chemical structures, high purity of materials, and outstanding repeatability from batch to batch synthesis. Remarkably, ASM OSCs with power conversion efficiency (PCE) beyond 13% were achieved by structure improvement of the electron donor and choosingY6as the electron acceptor. However, the fill factor (FF) is an obstacle that limits the further improvement of the PCE for these ASM OSCs. Herein, we focus on the FF improvement of recently reported ASM OSCs withBTR-Cl:Y6as the active layer by miscibility-induced active layer morphology optimization. The incorporation of fullerene derivatives, which have good miscibility with bothBTR-ClandY6, results in reduced bimolecular recombination and thus improved FF. In particular, whenca.5 wt% ofPC(71)BMwas added in the active layer, a FF of 77.11% was achieved without sacrificing the open circuit voltage (V-OC) and the short circuit current density (J(SC)), leading to a record PCE of 15.34% (certified at 14.7%) for ASM OSCs. We found that the optimized device showed comparable charge extraction, longer charge carrier lifetime, and slower bimolecular recombination rate compared with those of the control devices (w/o fullerene). Our results demonstrate that the miscibility driven regulation of active layer morphology by incorporation of a fullerene derivative delicately optimizes the active layer microstructures and improves the device performance, which brings vibrancy to OSC research.

A High Throughput Platform to Minimize Voltage and Fill Factor Losses - Haffner-Schirmer, Julian; Le Corre, Vincent Marc; Forberich, Karen; Egelhaaf, Hans-Joachim; Osterrieder, Tobias; Wortmann, Jonas; Liu, Chao; Weitz, Paul; Heumüller, Thomas; Bornschlegl, Andreas; Wachsmuth, Josua; Distler, Andreas; et al. (Advanced Energy Materials, 2025)
Organic photovoltaics (OPV) now can exceed 20% power conversion efficiency in single junction solar cells. To close the remaining gap to competing technologies, both fill factor and open-circuit voltage must be optimized. The Langevin reduction factor is a well-known concept that measures the degree to which charge extraction is favored over charge recombination. It is therefore ideally suited as an optimization target in high-throughput workflows; however, its evaluation so far requires expert interaction. Here, an integrated high-throughput workflow is presented, able to obtain the Langevin reduction factor within a few seconds with high accuracy without human intervention and thus suited for autonomous experiments. This is achieved by combining evidence from UV–vis spectra, current–voltage curves, and a novel implementation of microsecond transient absorption kinetics allowing, for the first time, the intrinsic determination of charge absorption cross-sections, which is crucial to reporting stationary charge densities. The method is demonstrated by varying the donor:acceptor ratio of the high performance OPV blend PM6:Y12. The high reproducibility of the method allows to find a strictly exponential relationship between the PM6 exciton energy and the Langevin reduction factor.
CRIS-Team Scopus Importer:2025-01-31
Keywords: charge dynamics; high throughput; Langevin reduction factor; organic photovoltaics; transient absorption kinetics

A polymer bilayer hole transporting layer architecture for high-efficiency and stable organic solar cells - Xu, Junyi; Heumüller, Thomas; Le Corre, Vincent Marc; Barabash, Anastasia; Félix, Roberto; Frisch, Johannes; Bär, Marcus; Brabec, Christoph (Joule, 2024)
All-solution-processed organic photovoltaic (OPV) cells allow cost- and energy-effective fabrication methods for large-area devices. Despite significant progress on laboratory-scale devices, there is still a lack of interface materials that can be solution processed on top of the active layer, are compatible with novel non-fullerene acceptors (NFAs), and also provide sufficient long-term stability. We developed a novel interface layer concept, where alcohol-based organic polymer nanoparticles can be processed on top of a polymer-NFA active layer and doped to achieve a quasi-Ohmic hole contact. Moreover, poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) is processed as a second layer, forming a bilayer solution-processed hole transporting layer (HTL), providing an industrially relevant inverted architecture with a protective PEDOT:PSS layer on top. Most importantly, exceptional stability is observed. PM6:Y6 devices with the bilayer HTL are demonstrated to maintain 93% of their initial efficiency for 1,800 h under continuous solar cell operation at 60°C.
CRIS-Team Scopus Importer:2024-10-11
Keywords: hole transport layer; nanoparticles; organic solar cell; solution-processed

Beginner's Guide to Visual Analysis of Perovskite and Organic Solar Cell Current Density–Voltage Characteristics - These, Albert; Koster, L. Jan Anton; Brabec, Christoph; Le Corre, Vincent Marc (Advanced Energy Materials, 2024)
The current density–voltage characteristic (J–V) is a critical tool for understanding the behavior of solar cells. This study presents an overview of the key aspects of J–V analysis and introduces a user-friendly flowchart that facilitates the swift identification of the most probable limiting process in a solar cell, based mainly on the outcomes of light-intensity-dependent J–V measurements. The flowchart is developed through extensive drift-diffusion simulations and a rigorous review of the literature, with a specific focus on perovskite and organic solar cells. Moreover, the flowchart proposes supplementary experiments that can be conducted to obtain a more precise prediction of the primary performance losses. It therefore serves as an optimal starting point to analyse performance losses of solar cells.
CRIS-Team Scopus Importer:2024-04-19
Keywords: current-voltage characteristic; drift-diffusion simulation; organic solar cell; perovskite solar cell; photovoltaics

Bilayer–ternary polymer solar cells fabricated using spontaneous spreading on water - Colberts, Fallon JM; Wienk, Martijn M; Heuvel, Ruurd; Li, Weiwei; Le Corre, Vincent Marc; Koster, L Jan Anton; Janssen, René AJ (Advanced Energy Materials, 2018)

Binary cations minimize energy loss in the wide-band-gap perovskite toward efficient all-perovskite tandem solar cells - Zhang, Kaicheng; Liu, Chao; Peng, Zijian; Li, Chaohui; Tian, Jingjing; Li, Canru; García Cerrillo, José; Dong, Lirong; Streller, Fabian; Späth, Andreas; Musiienko, Artem; Englhard, Jonas; et al. (Joule, 2024)
Perovskite-based tandem solar cells stand at the forefront of photovoltaic innovation due to their exceptional performance and cost-effective fabrication. This study focuses on minimizing energy losses within a 1.80 eV perovskite sub-cell. We demonstrate that the surface treatment of perovskite with binary guanidinium bromide and 4-fluorophenylammonium iodide synergistically reduces defect densities and adjusts interfacial energy-level alignment. The enhanced passivation effect and the formation of a surface dipole significantly reduce nonradiative recombination and transport losses, leading to a notable increase in the open-circuit voltage and fill factor product, thereby achieving an impressive power conversion efficiency (PCE) of 19.0%. The reproducibility of these findings is confirmed by consistent results across different laboratories. Furthermore, integration with a narrow-band-gap perovskite yields an all-perovskite tandem device with a PCE of 27.2%. This comprehensive understanding of the pivotal role of spacer cations in surface treatment significantly advances the pathway toward efficient perovskite photovoltaics.
CRIS-Team Scopus Importer:2024-08-30
Keywords: 2D phases; all-perovskite tandem solar cell; energy loss; energy-level alignment; nonradiative recombination; passivation; spacer cations; surface dipole; surface treatment; wide band-gap perovskite

Bypassing the Single Junction Limit with Advanced Photovoltaic Architectures - Lüer, Larry; Peters, Ian Marius; Le Corre, Vincent Marc; Forberich, Karen; Guldi, Dirk Michael; Brabec, Christoph (Advanced Materials, 2023)
Multijunction devices and photon up- and down-conversion are prominent concepts aimed at increasing photovoltaic efficiencies beyond the single junction limit. Integrating these concepts into advanced architectures may address long-standing issues such as processing complexity, microstructure control, and resilience against spectral changes of the incoming radiation. However, so far, no models have been established to predict the performance of such integrated architectures. Here, a simulation environment based on Bayesian optimization is presented, that can predict and virtually optimize the electrical performance of multi-junction architectures, both vertical and lateral, in combination with up- and down-conversion materials. Microstructure effects on performance are explicitly considered using machine-learned predictive models from high throughput experimentation on simpler architectures. Two architectures that would surpass the single junction limit of photovoltaic energy conversion at reasonable complexity are identified: a vertical “staggered half octave system,” where selective absorption allows the use of 6 different bandgaps, and the lateral “overlapping rainbow system” where selective irradiation allows the use of a narrowband energy acceptor with reduced voltage losses, according to the energy gap law. Both architectures would be highly resilient against spectral changes, in contrast with two terminal multi-junction architectures which are limited by Kirchhoff's law.<br

Carrier Transport and Recombination in Efficient "All-Small-Molecule" Solar Cells with the Nonfullerene Acceptor IDTBR - Liang, Ru‐Ze; Babics, Maxime; Savikhin, Victoria; Zhang, Weimin; Le Corre, Vincent Marc; Lopatin, Sergei; Kan, Zhipeng; Firdaus, Yuliar; Liu, Shengjian; Mcculloch, Iain; Toney, Michael F.; Beaujuge, Pierre M (Advanced Energy Materials, 2018)
Reaching device efficiencies that can rival those of polymer-fullerene Bulk Heterojunction (BHJ) solar cells (>10%) remains challenging with the ''All-Small-Molecule'' (All-SM) approach, in part because of (i) the morphological limitations that prevail in the absence of polymer and (ii) the difficulty to raise and balance out carrier mobilities across the active layer. In this report, the authors show that blends of the SM donor DR3TBDTT (DR3) and the nonfullerene SM acceptor O-IDTBR are conducive to ''All-SM'' BHJ solar cells with high open-circuit voltages (V-OC) >1.1 V and PCEs as high as 6.4% (avg. 6.1%) when the active layers are subjected to a post-processing solvent vapor-annealing (SVA) step with dimethyl disulfide (DMDS). Combining electron energy loss spectroscopy (EELS) analyses and systematic carrier recombination examinations, the authors show that SVA treatments with DMDS play a determining role in improving charge transport and reducing non-geminate recombination for the DR3:O-IDTBR system. Correlating the experimental results and device simulations, it is found that substantially higher BHJ solar cell efficiencies of >12% can be achieved if the IQE and carrier mobilities of the active layer are increased to >85% and >10(-4) cm(2) V-1 s(-1), respectively, while suppressing the recombination rate constant k to <10(-12) cm(3) s(-1).
Keywords: carrier recombination; charge transport; nonfullerene acceptors; small molecule solar cells; solvent vapor annealing

Charge Carrier Extraction in Organic Solar Cells Governed by Steady-State Mobilities - Le Corre, Vincent Marc; Rahimi Chatri, Azadeh; Doumon, Nutifafa Y.; Koster, L Jan Anton (Advanced Energy Materials, 2017)
Charge transport in organic photovoltaic (OPV) devices is often characterized by steady-state mobilities. However, the suitability of steady-state mobilities to describe charge transport has recently been called into question, and it has been argued that dispersion plays a significant role. In this paper, the importance of the dispersion of charge carrier motion on the performance of organic photovoltaic devices is investigated. An experiment to measure the charge extraction time under realistic operating conditions is set up. This experiment is applied to different blends and shows that extraction time is directly related to the geometrical average of the steady-state mobilities. This demonstrates that under realistic operating conditions the steady-state mobilities govern the charge extraction of OPV and gives a valuable insight in device performance.
Keywords: bulk-heterojunction solar cells; charge carrier extraction; organic photovoltaics; steady-state mobility

Charge Transport Layers Limiting the Efficiency of Perovskite Solar Cells: How To Optimize Conductivity, Doping, and Thickness - Le Corre, Vincent Marc; Stolterfoht, Martin; Perdigón-Toro, Lorena; Feuerstein, Markus; Wolff, Christian M; Gil-Escrig, Lidón; Bolink, Henk J; Neher, Dieter; Koster, L Jan Anton (ACS Applied Energy Materials, 2019)
Perovskite solar cells (PSCs) are one of the main research topics of the photovoltaic community; with efficiencies now reaching up to 24%, PSCs are on the way to catching up with classical inorganic solar cells. However, PSCs have not yet reached their full potential. In fact, their efficiency is still limited by nonradiative recombination, mainly via trap-states and by losses due to the poor transport properties of the commonly used transport layers (TLs). Indeed, state-of-the-art TLs (especially if organic) suffer from rather low mobilities, typically within 10(-5) and 10(-2) cm(-2) V-1 s(-1), when compared to the high mobilities, 1-10 cm(-2) V-1 s(-1), measured for perovskites. This work presents a comprehensive analysis of the effect of the mobility, thickness, and doping density of the transport layers based on combined experimental and modeling results of two sets of devices made of a solution-processed high-performing triple-cation (PCE approximate to 20%). The results are also cross-checked on vacuum-processed MAPbI(3) devices. From this analysis, general guidelines on how to optimize a TL are introduced and especially a new and simple formula to easily calculate the amount of doping necessary to counterbalance the low mobility of the TLs.
Keywords: perovskite solar cells; transport layers; conductivity; doping; charge transport

Controlling Intermediate Phase Formation to Enhance Photovoltaic Performance of Inverted FA-Based Perovskite Solar Cells - Li, Chaohui; Park, Hyoungwon; Qiu, Shudi; Streller, Fabian; Zhang, Kaicheng; Peng, Zijian; Byun, Jiwon; Tian, Jingjing; Maiti, Santanu; Xie, Zhiqiang; Dong, Lirong; Liu, Chao; et al. (ACS Energy Letters, 2024)
Formamidinium (FA)-based perovskites exhibit significant potential for highly efficient photovoltaics due to their promising optoelectronic properties and optimal bandgap. However, the undesired inactive phase arises from multiple crystal nucleation pathways formed by various intermediate phases during the film formation process, persistently accompanying it. FA-based perovskites frequently struggle to form uniform, highly crystalline films. This challenge complicates the development of reliable and highly reproducible crystallization processes for perovskites and the establishment of guidelines for controlling the α-phase formation. In this work, we investigate the role of poly(acrylonitril-co-methyl acrylate) (PAM) to simultaneously control nucleation and subsequent α-phase crystallization. This successfully demonstrates the regulation of oriented crystal growth through the creation of a PAM-PbI2 intermediate. Ultimately, PAM-modified p-i-n architecture devices obtain a promising power conversion efficiency (PCE) of 25.30%, with VOC (1.211 V), achieving 95% of the detailed balance limit. Additionally, PAM-modified devices maintain ≥90% of the initial efficiency for 1000 h under 1 sun and 65 °C operation.
CRIS-Team Scopus Importer:2024-11-22

Cutting “lab-to-fab” short: high throughput optimization and process assessment in roll-to-roll slot die coating of printed photovoltaics - Wagner, Michael; Distler, Andreas; Le Corre, Vincent Marc; Zapf, Simon; Baydar, Burak; Schmidt, Hans-Dieter; Heyder, Madeleine; Forberich, Karen; Lüer, Larry; Brabec, Christoph; Egelhaaf, Hans-Joachim (Energy and Environmental Science, 2023)
Commercialization of printed photovoltaics requires knowledge of the optimal composition and microstructure of the single layers, and the ability to control these properties over large areas under industrial conditions. While microstructure optimization can be readily achieved by lab scale methods, the transfer from laboratory scale to a pilot production line (“lab to fab”) is a slow and cumbersome process: first, the difficulty of operating structure-sensitive methods in-line impedes proper microstructure characterization, and second, the processing-functionality relationship must be redetermined for every material combination as the results obtained by typical lab-scale spin-coating cannot be directly transferred to other coating methods. Here, we show how we can optimize the performance of organic solar cells and at the same time assess process performance in a 2D combinatorial approach directly on an industrially relevant slot die coating line. This is enabled by a multi-nozzle slot die coating head allowing parameter variations along and across the web. This modification allows us to generate and analyze 3750 devices in a single coating run, varying the active layer donor : acceptor ratio and the thickness of the electron transport layer (ETL). We use Gaussian Process Regression (GPR) to exploit the whole dataset for precise determination of the optimal parameter combination. Performance-relevant features of the active layer morphology are inferred from UV-Vis absorption spectra. By mapping morphology in this way, small undesired gradients of process conditions (extrusion rates, annealing temperatures) are detected and their effect on device performance is quantified. The correlation between process parameters, morphology and performance obtained by GPR provides hints to the underlying physics, which are finally quantified by automated high-throughput drift-diffusion simulations. This leads to the conclusion that voltage losses which are observed for very thin ETL coatings are due to incomplete coverage of the electrode by the ETL, which causes enhanced surface recombination.
CRIS-Team Scopus Importer:2023-11-10

Device modeling of perovskite solar cells: insights and outlooks - Le Corre, Vincent Marc; Wang, Zishuai; Koster, L Jan Anton; Tress, Wolfgang (Soft-Matter Thin Film Solar Cells: Physical Processes and Device Simulation, 2020)

Effects of Fluorination on Fused Ring Electron Acceptor for Active Layer Morphology, Exciton Dissociation, and Charge Recombination in Organic Solar Cells - Hou, Licheng; Lv, Jie; Wobben, Friso; Le Corre, Vincent Marc; Tang, Hua; Singh, Ranbir; Kim, Min; Wang, Fufang; Sun, Haitao; Chen, Wenjing; Xiao, Zhengguo; Kumar, Manish; et al. (ACS Applied Materials and Interfaces, 2020)
Fluorination is one of the effective approaches to alter the organic semiconductor properties that impact the performance of the organic solar cells (OSCs). Positive effects of fluorination are also revealed in the application of fused ring electron acceptors (FREAs). However, in comparison with the efforts allocated to the material designs and power conversion efficiency enhancement, understanding on the excitons and charge carriers' behaviors in high-performing OSCs containing FREAs is limited. Herein, the impact of fluorine substituents on the active layer morphology, and therefore exciton dissociation, charge separation, and charge carriers' recombination processes are examined by fabricating OSCs with PTO2 as the donor and two FREAs, O-IDTT-IC and its fluorinated analogue O-IDTT-4FIC, as the acceptors. With the presence of O-IDTT-4FIC in the devices, it is found that the excitons dissociate more efficiently, and the activation energy required to split the excitons to free charge carriers is much lower; the charge carriers live longer and suffer less extent of trap-assisted recombination; the trap density is 1 order of magnitude lower than that of the nonfluorinated counterpart. Overall, these findings provide information about the complex impacts of FREA fluorination on efficiently performed OSCs.
Keywords: fluorination; exciton dissociations; activation energy; trap assisted recombination; crystallinity

Efficient Double- and Triple-Junction Nonfullerene Organic Photovoltaics and Design Guidelines for Optimal Cell Performance - Firdaus, Yuliar; Ho, Carr Hoi Yi; Lin, Yuanbao; Yengel, Emre; Le Corre, Vincent Marc; Nugraha, Mohamad I; Yarali, Emre; So, Franky; Anthopoulos, Thomas D (ACS Energy Letters, 2020)
The performance of multijunction devices lags behind single-junction organic photovoltaics (OPVs) mainly because of the lack of suitable subcells. Here, we attempt to address this bottleneck and demonstrate efficient nonfullerene-based multijunction OPVs while at the same time highlighting the remaining challenges. We first demonstrate double-junction OPVs with power conversion efficiency (PCE) of 16.5%. Going a step further, we developed triple-junction OPVs with a PCE of 14.9%, the highest value reported to date for this triple-junction cells. Device simulations suggest that improving the front-cell's carrier mobility to >5 X 10(-4) cm(2) V-1 s(-1) is needed to boost the efficiency of double- and triple-junction OPVs. Analysis of the efficiency limit of triple-junction devices predicts that PCE values of close to 26% are possible. To achieve this, however, the optical absorption and charge transport within the subcells would need to be optimized. The work is an important step toward next-generation multijunction OPVs.

Efficient, stable, and fully printed carbon-electrode perovskite solar cells enabled by hole-transporting bilayers - Du, Tian; Qiu, Shudi; Zhou, Xin; Le Corre, Vincent Marc; Wu, Mingjian; Dong, Lirong; Peng, Zijian; Zhao, Yicheng; Jang, Dongju; Spiecker, Erdmann; Brabec, Christoph; Egelhaaf, Hans-Joachim (Joule, 2023)
Printable planar carbon electrodes emerge as a promising replacement for thermally evaporated metals as the rear contact for perovskite solar cells (PSCs). However, the power conversion efficiencies (PCEs) of the state-of-the-art carbon-electrode PSC (c-PSC) noticeably lag behind their metal-electrode counterparts. Here, we propose a hole-transporting bilayer (HTbL) configuration to improve the fill factor and the open-circuit voltage of c-PSCs simultaneously. The HTbL is prepared by sequentially blade coating two organic semiconductors between perovskite and carbon, with the outer HTL enhancing hole extraction to carbon, while the inner HTL mitigates perovskite surface recombination. Consequently, our fully printed c-PSCs with HTbL outperform those with single HTL, and a stabilized champion PCE of 19.2% is achieved compared with that of 17.3%. Our prototype c-PSC stably operates during 1 sun, 65°C aging test (ISOS-L-2I) for 2,500 h showing negligible PCE drop, validating its potential as a highly cost-effective photovoltaic technology.
CRIS-Team Scopus Importer:2023-08-18
Keywords: bilayer; carbon electrode; fully printed perovskite solar cells; hole transporting; stability

Fully printed flexible perovskite solar modules with improved energy alignment by tin oxide surface modification - Dong, Lirong; Qiu, Shudi; García Cerrillo, José; Wagner, Michael; Kasian, Olga; Feroze, Sarmad; Jang, Dongju; Li, Chaohui; Le Corre, Vincent Marc; Zhang, Kaicheng; Peisert, Heiko; U. Kosasih, Felix; et al. (Energy and Environmental Science, 2024)
Fully printed flexible perovskite solar cells (f-PSCs) show great potential for the commercialization of perovskite photovoltaics owing to their compatibility with high-throughput roll-to-roll (R2R) production. However, the challenge remains in the deficiency in controlling interfacial recombination losses of the functional layer, causing remarkable loss of power conversion efficiency (PCE) in industrial production. Here, a fullerene-substituted alkylphosphonic acid dipole layer is introduced between the R2R-printed tin oxide electron transport layer and the perovskite active layer to reduce the energetic barrier and to suppress surface recombination at the buried interface. The resulting f-PSCs exhibit a PCE of 17.0% with negligible hysteresis, retain 95% of their initial PCE over 3000 bending cycles and achieve a T95 lifetime of 1200 h under 1 sun and 65 °C in nitrogen atmosphere. Moreover, the fully printed flexible perovskite solar mini-modules (f-PSMs) with a 20.25 cm2 aperture area achieve a PCE of 11.6%. The encapsulated f-PSMs retain 90% of their initial PCE after 500 h damp-heat testing at 65 °C and 85% relative humidity (ISOS-D3). This work marks an important progress toward the realization of efficient and stable flexible perovskite photovoltaics for commercialization.
CRIS-Team Scopus Importer:2024-08-16

Homo-Tandem Polymer Solar Cells with V-OC > 1.8 V for Efficient PV-Driven Water Splitting - Gao, Yangqin; Le Corre, Vincent Marc; Gaïtis, Alexandre; Neophytou, Marios; Hamid, Mahmoud Abdul; Takanabe, Kazuhiro; Beaujuge, Pierre M (Advanced Materials, 2016)

Identification of the dominant recombination process for perovskite solar cells based on machine learning - Le Corre, Vincent Marc; Sherkar, Tejas S; Koopmans, Marten; Koster, L Jan Anton (Cell Reports Physical Science, 2021)
Over the past decade, perovskite solar cells have become one of the major research interests of the photovoltaic community, and they are now on the brink of catching up with the classical inorganic solar cells, with efficiency now reaching up to 25%. However, significant improvements are still achievable by reducing recombination losses. The aim of this work is to develop a fast and easy-to-use tool to pinpoint the main losses in perovskite solar cells. We use large-scale drift-diffusion simulations to get a better understanding of the light intensity dependence of the open-circuit voltage and how it correlates to the dominant recombination process. We introduce an automated identification tool using machine learning methods to pinpoint the dominant loss using the light intensity-dependent performances as an input. The machine learning was trained using >2 million simulations and gives an accuracy of the prediction up to 82%.

Impact of Electrodes on Recombination in Bulk Heterojunction Organic Solar Cells - Rahimi Chatri, Azadeh; Torabi, Solmaz; Le Corre, Vincent Marc; Koster, L Jan Anton (ACS Applied Materials and Interfaces, 2018)
In recent years, the efficiency of organic solar cells (OSCs) has increased to more than 13%, although different barriers are on the way for reaching higher efficiencies. One crucial barrier is the recombination of charge carriers, which can either occur as the bulk recombination of photogenerated charges or the recombination of photogenerated charges and electrodic induced charges (EICs). This work studies the impact of EICs on the recombination lifetime in OSCs. To this end, the net recombination lifetime of photogenerated charge carriers in the presence of EICs is measured by means of conventional and newly developed transient photovoltage techniques. Moreover, a new approach has been introduced to exclusively measure the bulk recombination lifetime, i.e., in the absence of EICs; this approach was conducted by depositing transparent insulating layers on both sides of the OSC active layer. An examination of these approaches on OSCs with different active layer materials, thicknesses, and varying light intensities determined that the EICs can only reduce the recombination lifetime of the photogenerated charges in OSCs with very weak recombination strength. This work supports that for OSCs with highly reduced recombination strength, eliminating the recombination of photogenerated charges and EICs is critical for achieving better performance. Therefore, the use of a proper blocking layer suppresses EIC recombination in systems with very weak recombination.
Keywords: organic solar cells; recombination lifetime; induced charges; blocking layers; bulk heterojunction

In Situ Probing the Crystallization Kinetics in Gas-Quenching-Assisted Coating of Perovskite Films - Qiu, Shudi; Majewski, Martin; Dong, Lirong; Jang, Dongju; Le Corre, Vincent Marc; García Cerrillo, José; Ronsin, Olivier J.J.; Yang, Fu; Guo, Fei; Zhang, Kaicheng; Lüer, Larry; Harting, Jens; et al. (Advanced Energy Materials, 2024)
The pursuit of commercializing perovskite photovoltaics is driving the development of various scalable perovskite crystallization techniques. Among them, gas quenching is a promising crystallization approach for high-throughput deposition of perovskite films. However, the perovskite films prepared by gas-quenching assisted blade coating are susceptible to the formation of pinholes and frequently show inferior crystallinity if the interplay between film coating, film drying, and crystallization kinetics is not fully optimized. That arguably requires a thorough understanding of how single processing steps influence the crystallization kinetics of printed perovskite films. Here, in situ optical spectroscopies are integrated into a doctor-blading setup that allows to real-time monitor film formation during the gas-quenching process. It is found that the essential role of gas quenching treatment is in achieving a smooth and compact perovskite film by controlling the nucleation rate. Moreover, with the assistance of phase-field simulations, the role of excessive methylammonium iodide is revealed to increase grain size by accelerating the crystal growth rate. These results show a tailored control of crystal growth rate is critical to achieving optimal film quality, leading to fully printed solar cells with a champion power conversion efficiency of 19.50% and mini solar modules with 15.28% efficiency are achieved.
CRIS-Team Scopus Importer:2024-01-12
Keywords: blade coating; fully printed perovskite photovoltaics; gas quenching; in situ techniques; phase-field simulations

Ion-induced field screening as a dominant factor in perovskite solar cell operational stability - Thiesbrummel, Jarla; Shah, Sahil; Gutierrez-Partida, Emilio; Zu, Fengshuo; Peña-Camargo, Francisco; Zeiske, Stefan; Diekmann, Jonas; Ye, Fangyuan; Peters, Karol P.; Brinkmann, Kai O.; Caprioglio, Pietro; Dasgupta, Akash; et al. (Nature Energy, 2024)
The presence of mobile ions in metal halide perovskites has been shown to adversely affect the intrinsic stability of perovskite solar cells (PSCs). However, the actual contribution of mobile ions to the total degradation loss compared with other factors such as trap-assisted recombination remains poorly understood. Here we reveal that mobile ion-induced internal field screening is the dominant factor in the degradation of PSCs under operational conditions. The increased field screening leads to a decrease in the steady-state efficiency, often owing to a large reduction in the current density. Instead, the efficiency at high scan speeds (>1,000 V s−1), where the ions are immobilized, is much less affected. We also show that the bulk and interface quality do not degrade upon ageing, yet the open-circuit voltage decreases owing to an increase in the mobile ion density. This work reveals the importance of ionic losses for intrinsic PSC degradation before chemical or extrinsic mechanical effects manifest.
CRIS-Team Scopus Importer:2024-04-05

Key Parameters Requirements for Non-Fullerene-Based Organic Solar Cells with Power Conversion Efficiency > 20% - Firdaus, Yuliar; Le Corre, Vincent Marc; Khan, Jafar I.; Kan, Zhipeng; Laquai, Frederic; Beaujuge, Pierre M; Anthopoulos, Thomas D (Advanced Science, 2019)
The reported power conversion efficiencies (PCEs) of nonfullerene acceptor (NFA) based organic photovoltaics (OPVs) now exceed 14% and 17% for single-junction and two-terminal tandem cells, respectively. However, increasing the PCE further requires an improved understanding of the factors limiting the device efficiency. Here, the efficiency limits of single-junction and two-terminal tandem NFA-based OPV cells are examined with the aid of a numerical device simulator that takes into account the optical properties of the active material(s), charge recombination effects, and the hole and electron mobilities in the active layer of the device. The simulations reveal that single-junction NFA OPVs can potentially reach PCE values in excess of 18% with mobility values readily achievable in existing material systems. Furthermore, it is found that balanced electron and hole mobilities of >10(-3) cm(2) V-1 s(-1) in combination with low nongeminate recombination rate constants of 10(-12) cm(3) s(-1) could lead to PCE values in excess of 20% and 25% for single-junction and two-terminal tandem OPV cells, respectively. This analysis provides the first tangible description of the practical performance targets and useful design rules for single-junction and tandem OPVs based on NFA materials, emphasizing the need for developing new material systems that combine these desired characteristics.
Keywords: bulk-heterojunction solar cells; drift-diffusion model; nonfullerene acceptors; numerical device simulations; organic photovoltaics; tandem devices

Long-range exciton diffusion in molecular non-fullerene acceptors - Firdaus, Yuliar; Le Corre, Vincent Marc; Karuthedath, Safakath; Liu, Wenlan; Markina, Anastasia; Huang, Wentao; Chattopadhyay, Shirsopratim; Nahid, Masrur Morshed; Nugraha, Mohamad I; Lin, Yuanbao; Seitkhan, Akmaral; Basu, Aniruddha; et al. (Nature Communications, 2020)
The short exciton diffusion length associated with most classical organic semiconductors used in organic photovoltaics (5-20nm) imposes severe limits on the maximum size of the donor and acceptor domains within the photoactive layer of the cell. Identifying materials that are able to transport excitons over longer distances can help advancing our understanding and lead to solar cells with higher efficiency. Here, we measure the exciton diffusion length in a wide range of nonfullerene acceptor molecules using two different experimental techniques based on photocurrent and ultrafast spectroscopy measurements. The acceptors exhibit balanced ambipolar charge transport and surprisingly long exciton diffusion lengths in the range of 20 to 47nm. With the aid of quantum-chemical calculations, we are able to rationalize the exciton dynamics and draw basic chemical design rules, particularly on the importance of the end-group substituent on the crystal packing of nonfullerene acceptors.

Novel wide-bandgap non-fullerene acceptors for efficient tandem organic solar cells - Firdaus, Yuliar; He, Qiao; Lin, Yuanbao; Nugroho, Ferry Anggoro Ardy; Le Corre, Vincent Marc; Yengel, Emre; Balawi, Ahmed H; Seitkhan, Akmaral; Laquai, Frederic; Langhammer, Christoph; Liu, Feng; Heeney, Martin; et al. (Journal of Materials Chemistry A, 2020)
The power conversion efficiency (PCE) of tandem organic photovoltaics (OPVs) is currently limited by the lack of suitable wide-bandgap materials for the front-cell. Here, two new acceptor molecules, namely IDTA and IDTTA, with optical bandgaps (Eoptg) of 1.90 and 1.75 eV, respectively, are synthesized and studied for application in OPVs. When PBDB-T is used as the donor polymer, single-junction cells with PCE of 7.4%, for IDTA, and 10.8%, for IDTTA, are demonstrated. The latter value is the highest PCE reported to date for wide-bandgap (Eoptg >= 1.7 eV) bulk-heterojunction OPV cells. The higher carrier mobility in IDTTA-based cells leads to improved charge extraction and higher fill-factor than IDTA-based devices. Moreover, IDTTA-based OPVs show significantly improved shelf-lifetime and thermal stability, both critical for any practical applications. With the aid of optical-electrical device modelling, we combined PBDB-T:IDTTA, as the front-cell, with PTB7-Th:IEICO-4F, as the back-cell, to realize tandem OPVs with open circuit voltage of 1.66 V, short circuit current of 13.6 mA cm(-2) and a PCE of 15%; in excellent agreement with our theoretical predictions. The work highlights IDTTA as a promising wide-bandgap acceptor for high-performance tandem OPVs.

Observation of reversible light degradation in organic photovoltaics induced by long-persistent radicals - Zhang, Difei; Liu, Chao; Zhang, Kaicheng; Jia, Yanhua; Zhong, Wenkai; Qiu, Weidong; Li, Yuanfeng; Heumüller, Thomas; Forberich, Karen; Le Corre, Vincent Marc; Lüer, Larry; Li, Ning; et al. (Energy and Environmental Science, 2023)
With the rapid development of organic photovoltaics, device stability has become a crucial obstacle hindering their transition from laboratory-scale to industrial applications. However, it still remains unclear how light differs from heat in driving trap formation and device degradation. On the basis of the PTzBI-dF:Y6-BO system, it is observed that the post-thermal annealing on these high-performance organic solar cells can partially recover the light-induced burn-in losses. The recovery process is found to be correlated with a reversible charge extraction ability, reversible trap density of state, local charge carrier density and charge accumulation. Herein, we propose an innovative mechanism for light degradation in organic photovoltaic devices, which is triggered by the presence of light-induced long-persistent radicals. The findings offer deep insights into light degradation of organic photovoltaics and a new perspective for improving device stability under long-term operation.
CRIS-Team Scopus Importer:2023-12-01

Over one-micron-thick void-free perovskite layers enable highly efficient and fully printed solar cells - Qiu, Shudi; Majewski, Martin; Dong, Lirong; Distler, Andreas; Li, Chaohui; Forberich, Karen; Tian, Jingjing; Hemasiri, Naveen Harindu; Liu, Chao; Zhang, Jiyun; Yang, Fu; Le Corre, Vincent Marc; et al. (Energy and Environmental Science, 2025)
Commercialization of perovskite photovoltaics hinges on the successful transition from laboratory-scale fabrication to industrial-scale manufacturing. A key challenge in fully printed perovskite solar cells with non-reflecting back electrodes is the deposition of high-quality, over-one-micron-thick perovskite layers to minimize photocurrent losses from incomplete light absorption. However, the formation of voids at the substrate/perovskite interface impedes the fabrication of such layers. Here, phase-field simulations reveal that the bottom voids originate from trapped residual solvents, driven by nanocrystal aggregation at the liquid-vapor interface during drying. Guided by these insights, we introduce a two-dimensional (2D) perovskite layer-assisted growth strategy to promote heterogeneous nucleation at the substrate, accelerating 3D perovskite crystallization and preventing solvent entrapment. This strategy enables the formation of highly crystalline, monolithic perovskite films exceeding one micrometer in thickness. The resulting void-free films maximize photocurrent extraction, achieving power conversion efficiencies of 19.9% on rigid substrates and 17.5% on flexible substrates in fully printed perovskite solar cells with non-reflecting carbon electrodes.
CRIS-Team Scopus Importer:2025-05-30

Pathways toward 30% Efficient Single-Junction Perovskite Solar Cells and the Role of Mobile Ions - Diekmann, Jonas; Caprioglio, Pietro; Futscher, Moritz H; Le Corre, Vincent Marc; Reichert, Sebastian; Jaiser, Frank; Arvind, Malavika; Perdigón-Toro, Lorena; Gutierrez-Partida, Emilio; Peña-Camargo, Francisco; Deibel, Carsten; Ehrler, Bruno; et al. (Solar RRL, 2021)
Perovskite semiconductors have demonstrated outstanding external luminescence quantum yields, enabling high power conversion efficiencies (PCEs). However, the precise conditions to advance to an efficiency regime above monocrystalline silicon cells are not well understood. Herein, a simulation model that describes efficient p-i-n-type perovskite solar cells well and a range of different experiments is established. Then, important device and material parameters are studied and it is found that an efficiency regime of 30% can be unlocked by optimizing the built-in voltage across the perovskite layer using either highly doped (10(19) cm(-3)) transport layers (TLs), doped interlayers or ultrathin self-assembled monolayers. Importantly, only parameters that have been reported in recent literature are considered, that is, a bulk lifetime of 10 mu s, interfacial recombination velocities of 10 cm s(-1), a perovskite bandgap (E-gap) of 1.5 eV, and an external quantum efficiency (EQE) of 95%. A maximum efficiency of 31% is predicted for a bandgap of 1.4 eV. Finally, it is demonstrated that the relatively high mobile ion density does not represent a significant barrier to reach this efficiency regime. The results of this study suggest continuous PCE improvements until perovskites may become the most efficient single-junction solar cell technology in the near future.
Keywords: perovskite solar cells; solar cell hysteresis; solar cell simulations; transport-layer doping

Photostability of Fullerene and Non-Fullerene Polymer Solar Cells: The Role of the Acceptor - Doumon, Nutifafa Y.; Dryzhov, Mikhail V; Houard, Félix V; Le Corre, Vincent Marc; Rahimi Chatri, Azadeh; Christodoulis, Panagiotis; Koster, L Jan Anton (ACS Applied Materials and Interfaces, 2019)
Recently, the advent of non-fullerene acceptors (NFAs) made it possible for organic solar cells (OSCs) to break the 10% efficiency barrier hardly attained by fullerene acceptors (FAs). In the past five years alone, more than hundreds of NFAs with applications in organic photovoltaics (OPVs) have been synthesized, enabling a notable current record efficiency of above 15%. Hence, there is a shift in interest toward the use of NFAs in OPVs. However, there has been little work on the stability of these new materials in devices. More importantly, there is very little comparative work on the photostability of FA versus NFA solar cells to ascertain the pros and cons of the two systems. Here, we show the photostability of solar cells based on two workhorse acceptors, in both conventional and inverted structures, namely, ITIC (as NFA) and [70]PCBM (as FA), blended with either PBDB-T or PTB7-Th polymer. We found that, irrespective of the polymer, the cell structure, or the initial efficiency, the [70]PCBM devices are more photostable than the ITIC ones. This observation, however, opposes the assumption that NFA solar cells are more photochemically stable. These findings suggest that complementary absorption should not take precedence in the design rules for the synthesis of new molecules and there is still work left to be done to achieve stable and efficient OSCs.
Keywords: Fullerene derivatives; Non-Fullerene acceptors; Degradation; Organic solar cells; Photostability

Precise control of process parameters for >23% efficiency perovskite solar cells in ambient air using an automated device acceleration platform - Zhang, Jiyun; Wu, Jianchang; Barabash, Anastasia; Du, Tian; Qiu, Shudi; Le Corre, Vincent Marc; Zhao, Yicheng; Zhang, Kaicheng; Schmitt, Frederik; Peng, Zijian; Tian, Jingjing; Li, Chaohui; et al. (Energy and Environmental Science, 2024)
Achieving high-performance perovskite photovoltaics, especially in ambient air, is critically dependent on the precise optimization of process parameters. However, traditional manual methods often struggle to effectively control the key variables. This inherent challenge requires a paradigm shift toward automated platforms capable of precise and reproducible experiments. Herein, we use a fully automated device acceleration platform (DAP) to optimize air-processed parameters for preparing perovskite devices using a two-step sequential deposition technique. Over ten process parameters with significant potential to influence device performance are systematically optimized. Specifically, we delve into the impact of the dripping speed of organic ammonium halide, a parameter that is difficult to control manually, on both perovskite film and device performance. Through the targeted design of experiments, we reveal that the dripping speed significantly affects device performance primarily by adjusting the residual PbI2 content in the films. We find that optimal dripping speeds, such as 50 µL s−1, contribute to top-performance devices. Conversely, excessively fast or slow speeds result in devices with comparatively poorer performance and lower reproducibility. The optimized parameter set enables us to establish a standard operation procedure (SOP) for additive-free perovskite processing in ambient conditions, which yield devices with efficiencies surpassing 23%, satisfactory reproducibility, and state-of-the-art photo-thermal stability. This research underscores the importance of understanding the causality of process parameters in enhancing perovskite photovoltaic performance. Furthermore, our study highlights the pivotal role of automated platforms in discovering innovative workflows and accelerating the development of high-performing perovskite photovoltaic technologies.
CRIS-Team Scopus Importer:2024-07-19

Quantification of Efficiency Losses Due to Mobile Ions in Perovskite Solar Cells via Fast Hysteresis Measurements - Le Corre, Vincent Marc; Diekmann, Jonas; Peña‐Camargo, Francisco; Thiesbrummel, Jarla; Tokmoldin, Nurlan; Gutierrez-Partida, Emilio; Peters, Karol Pawel; Perdigón-Toro, Lorena; Futscher, Moritz H; Lang, Felix; Warby, Jonathan; Snaith, Henry J.; et al. (Solar RRL, 2022)
Perovskite semiconductors differ from most inorganic and organic semiconductors due to the presence of mobile ions in the material. Although the phenomenon is intensively investigated, important questions such as the exact impact of the mobile ions on the steady-state power conversion efficiency (PCE) and stability remain. Herein, a simple method is proposed to estimate the efficiency loss due to mobile ions via "fast-hysteresis" measurements by preventing the perturbation of mobile ions out of their equilibrium position at fast scan speeds (approximate to 1000 V s(-1)). The "ion-free" PCE is between 1% and 3% higher than the steady-state PCE, demonstrating the importance of ion-induced losses, even in cells with low levels of hysteresis at typical scan speeds (approximate to 100mv s(-1)). The hysteresis over many orders of magnitude in scan speed provides important information on the effective ion diffusion constant from the peak hysteresis position. The fast-hysteresis measurements are corroborated by transient charge extraction and capacitance measurements and numerical simulations, which confirm the experimental findings and provide important insights into the charge carrier dynamics. The proposed method to quantify PCE losses due to field screening induced by mobile ions clarifies several important experimental observations and opens up a large range of future experiments.
Keywords: hysteresis; mobile ions; perovskite solar cells

Reliability of charge carrier recombination data determined with charge extraction methods - Kniepert, Juliane; Paulke, Andreas; Perdigón-Toro, Lorena; Kurpiers, Jona; Zhang, Huotian; Gao, Feng; Yuan, Jun; Zou, Yingping; Le Corre, Vincent Marc; Koster, L Jan Anton; Neher, Dieter (Journal of Applied Physics, 2019)
Charge extraction methods are popular for measuring the charge carrier density in thin film organic solar cells and to draw conclusions about the order and coefficient of nongeminate charge recombination. However, results from such studies may be falsified by inhomogeneous steady state carrier profiles or surface recombination. Here, we present a detailed drift-diffusion study of two charge extraction methods, bias-assisted charge extraction (BACE) and time-delayed collection field (TDCF). Simulations are performed over a wide range of the relevant parameters. Our simulations reveal that both charge extraction methods provide reliable information about the recombination order and coefficient if the measurements are performed under appropriate conditions. However, results from BACE measurements may be easily affected by surface recombination, in particular for small active layer thicknesses and low illumination densities. TDCF, on the other hand, is more robust against surface recombination due to its transient nature but also because it allows for a homogeneous high carrier density to be inserted into the active layer. Therefore, TDCF is capable to provide meaningful information on the order and coefficient of recombination even if the model conditions are not exactly fulfilled. We demonstrate this for an only 100 nm thick layer of a highly efficient nonfullerene acceptor (NFA) blend, comprising the donor polymer PM6 and the NFA Y6. TDCF measurements were performed as a function of delay time for different laser fluences and bias conditions. The full set of data could be consistently fitted by a strict second order recombination process, with a bias- and fluence-independent bimolecular recombination coefficient k(2) = 1.7 x 10(-17)m(3) s(-1). BACE measurements performed on the very same layer yielded the identical result, despite the very different excitation conditions. This proves that recombination in this blend is mostly through processes in the bulk and that surface recombination is of minor importance despite the small active layer thickness. Published under license by AIP Publishing.

Response to Comment on "Charge Carrier Extraction in Organic Solar Cells Governed by Steady-State Mobilities" - Le Corre, Vincent Marc; Rahimi Chatri, Azadeh; Doumon, Nutifafa Y.; Koster, L Jan Anton (Advanced Energy Materials, 2018)

Revealing Charge Carrier Mobility and Defect Densities in Metal Halide Perovskites via Space-Charge-Limited Current Measurements - Le Corre, Vincent Marc; Duijnstee, Elisabeth A; El Tambouli, Omar; Ball, James M; Snaith, Henry J.; Lim, Jongchul; Koster, L Jan Anton (ACS Energy Letters, 2021)
Space-charge-limited current (SCLC) measurements have been widely used to study the charge carrier mobility and trap density in semiconductors. However, their applicability to metal halide perovskites is not straightforward, due to the mixed ionic and electronic nature of these materials. Here, we discuss the pitfalls of SCLC for perovskite semiconductors, and especially the effect of mobile ions. We show, using driftdiffusion (DD) simulations, that the ions strongly affect the measurement and that the usual analysis and interpretation of SCLC need to be refined. We highlight that the trap density and mobility cannot be directly quantified using classical methods. We discuss the advantages of pulsed SCLC for obtaining reliable data with minimal influence of the ionic motion. We then show that fitting the pulsed SCLC with DD modeling is a reliable method for extracting mobility, trap, and ion densities simultaneously. As a proof of concept, we obtain a trap density of 1.3 x 10(13) cm(-3), an ion density of 1.1 x 10(13) cm(-3), and a mobility of 13 cm(2) V-1 s(-1) for a MAPbBr(3) single crystal.

Revealing Degradation Mechanisms in 3D/2D Perovskite Solar Cells under Photothermal Accelerated Ageing - Peng, Zijian; Vincze, Andrej; Streller, Fabian; Le Corre, Vincent Marc; Zhang, Kaicheng; Li, Chaohui; Tian, Jingjing; Liu, Chao; Luo, Junsheng; Zhao, Yicheng; Späth, Andreas; Fink, Rainer; et al. (Energy and Environmental Science, 2024)
Three-dimensional/two-dimensional (3D/2D) heterojunctions in perovskite solar cells exhibit excellent optoelectronic properties and enhanced stability under mild ageing conditions. However, their performance degrades drastically under harsh ageing conditions. This study reveals the intrinsic instability of mono-ammonium based 2D perovskites (2D-mono) under photo-thermal ageing, which decompose into PbI2 and metallic lead (Pb0). The structural collapse promotes vacancy formation and facilitates iodide migration to the anode. As a result, it triggers a redox reaction that reduces the transport layer’s mobility and doping concentration, leading to a significant increase in series resistance. Compared to mono-ammonium-2D structure, di-ammonium-2D (2D-di) based interfaces demonstrate superior structural stability and effectively block iodide migration into the transporting layer. However, blocking-induced uneven iodide distribution leads to interstitial defect formation in the 3D layer, exacerbating non-radiative recombination. To address it, we propose a strategical method by incorporating 2D-di in the 3D bulk instead of on the top surface, which effectively confines mobile ions within the grain and suppresses cation phase segregation. This optimization yields stable perovskite solar cells with an extrapolated operational T80 lifetime exceeding 560 hours under harsh conditions (85°C and 2-sun illumination

Revealing Photodegradation Pathways of Organic Solar Cells by Spectrally Resolved Accelerated Lifetime Analysis - Weitz, Paul; Le Corre, Vincent Marc; Du, Xiaoyan; Forberich, Karen; Deibel, Carsten; Brabec, Christoph; Heumüller, Thomas (Advanced Energy Materials, 2022)
A method for organic solar cell (OSC) stability testing is presented that aims to provide more unique insight into the causes of degradation patterns of OSCs. The method involves using monochromatic light at high irradiation doses to accelerate isolated degradation mechanisms while monitoring the device with a series of in-situ steady-state and transient electrical measurements. The experimental results are accompanied by drift-diffusion simulations to localize degradation pathways. PM6:Y6-based OSCs are tested, which are known to show a rather broad range of lifetimes as a function of device architecture, material batches, or degradation conditions. The experiments reveal a degradation mechanism that causes an increased trap-state density inside the PM6:Y6 layer. The transient simulations suggest that these states are formed at or around the interface between the PM6:Y6 and the electron transport layer. Furthermore, the surprisingly dominant impact of the illuminating wavelength on the degradation pattern is evidenced. Lastly, the degradation rate of the devices scales linearly with light intensity, making high intensity and spectrally selective degradation the most promising way to accelerate stability testing for the faster development of stable OSCs.
CRIS-Team Scopus Importer:2022-12-09
Keywords: acceleration; drift-diffusion; organic solar cells; photodegradation; transient; wavelength-dependence

Revealing the doping density in perovskite solar cells and its impact on device performance - Peña-Camargo, Francisco; Thiesbrummel, Jarla; Hempel, Hannes; Musiienko, Artem; Le Corre, Vincent Marc; Diekmann, Jonas; Warby, Jonathan; Unold, Thomas; Lang, Felix; Neher, Dieter; Stolterfoht, Martin (Applied Physics Reviews, 2022)
Traditional inorganic semiconductors can be electronically doped with high precision. Conversely, there is still conjecture regarding the assessment of the electronic doping density in metal-halide perovskites, not to mention of a control thereof. This paper presents a multifaceted approach to determine the electronic doping density for a range of different lead-halide perovskite systems. Optical and electrical characterization techniques, comprising intensity-dependent and transient photoluminescence, AC Hall effect, transfer-length-methods, and charge extraction measurements were instrumental in quantifying an upper limit for the doping density. The obtained values are subsequently compared to the electrode charge per cell volume under short-circuit conditions (C U bi/e V), which amounts to roughly 1016 cm-3. This figure of merit represents the critical limit below which doping-induced charges do not influence the device performance. The experimental results consistently demonstrate that the doping density is below this critical threshold (∼1012 cm-3, which means â‰ª C U bi/e V) for all common lead-based metal-halide perovskites. Nevertheless, although the density of doping-induced charges is too low to redistribute the built-in voltage in the perovskite active layer, mobile ions are present in sufficient quantities to create space-charge-regions in the active layer, reminiscent of doped pn-junctions. These results are well supported by drift-diffusion simulations, which confirm that the device performance is not affected by such low doping densities.
CRIS-Team Scopus Importer:2022-06-10

Rough Electrode Creates Excess Capacitance in Thin-Film Capacitors - Torabi, Solmaz; Cherry, Megan; Duijnstee, Elisabeth A; Le Corre, Vincent Marc; Qiu, Li; Hummelen, Jan C; Palasantzas, George; Koster, L Jan Anton (ACS Applied Materials and Interfaces, 2017)
The parallel-plate capacitor equation is widely used in contemporary material research for nanoscale applications and nanoelectronics. To apply this equation, flat and smooth electrodes are assumed for a capacitor. This essential assumption is often violated for thin-film capacitors because the formation of nanoscale roughness at the electrode interface is very probable for thin films grown via common deposition methods. In this work, we experimentally and theoretically show that the electrical capacitance of thin-film capacitors with realistic interface roughness is significantly larger than the value predicted by the parallel-plate capacitor equation. The degree of the deviation depends on the strength of the roughness, which is described by three roughness parameters for a self-affine fractal surface. By applying an extended parallel plate capacitor equation that includes the roughness parameters of the electrode, we are able to calculate the excess capacitance of the electrode with weak roughness. Moreover, we introduce the roughness parameter limits for which the simple parallel-plate capacitor equation is sufficiently accurate for capacitors with one rough electrode. Our results imply that the interface roughness beyond the proposed limits cannot be dismissed unless the independence of the capacitance from the interface roughness is experimentally demonstrated. The practical protocols suggested in our work for the reliable use of the parallel-plate capacitor equation can be applied as general guidelines in various fields of interest.
Keywords: parallel-plate capacitor equation; interface roughness; dielectric constant; capacitance; thin-film capacitors

Simplifying contact-layer design for high-throughput printing of flexible perovskite photovoltaics - Dong, Lirong; Qiu, Shudi; Feroze, Sarmad; Wagner, Michael; Kasian, Olga; Peisert, Heiko; Kosasih, Felix U.; Ducati, Caterina; García Cerrillo, José; Tian, Jingjing; Li, Chaohui; Jang, Dongju; et al. (Energy and Environmental Science, 2024)
The realization of scalable roll-to-roll production processes for metal-halide perovskite modules is a necessary development for transferring developments and technologies from the lab to the fab. Before that, it is imperative to close the efficiency gap not only between the devices fabricated on rigid substrates versus flexible substrates, but also between solar cells to solar modules. In this regard, a critical assessment of device architectures that are more compatible to scalable fabrication is needed. Obviously, the adaption to mass manufacturing must not negatively impact device performance and operational stability. Here, by investigating the properties of printed fullerene-based phosphonic acid dipole interface layers, we establish simplified self-assembled monolayer (SAM) based n-i-p architectures without any charge extraction layers other than SAMs, which are easily processed and are thus ideally suited for mass production. We show that a contact-layer design with a printed fullerene-based SAM that has phosphonic acid is sufficient to provide good charge selectivity and to minimize interface recombination at the bottom electrode. We further show that the same SAM molecule can be used as a p-type interface material on top of the perovskite. This simplified contact-layer design, which is based on one material for both hole and electron work-function adaption is successfully integrated into our fully printed module process comprising the deposition of a carbon top electrode. The achieved open-circuit voltage exceeds 1.1 V, and the fill factor surpasses 70%, highlighting the potential of this novel interface design concept for both rigid and flexible substrates.
CRIS-Team Scopus Importer:2024-09-06

SIMsalabim: An open-source drift-diffusion simulator for semiconductor devices - Koopmans, Marten; Le Corre, Vincent Marc; Koster, L Jan Anton (Journal of Open Source Software, 2022)

Simulation of perovskite thin layer crystallization with varying evaporation rates - Majewski, M.; Qiu, Shudi; Ronsin, O.; Lüer, Larry; Le Corre, Vincent Marc; Du, Tian; Brabec, Christoph; Egelhaaf, Hans-Joachim; Harting, J. (Materials Horizons, 2024)
Perovskite solar cells (PSC) are promising potential competitors to established photovoltaic technologies due to their superior efficiency and low-cost solution processability. However, the limited understanding of the crystallization behaviour hinders the technological transition from lab-scale cells to modules. In this work, advanced phase field (PF) simulations of solution-based film formation are used for the first time to obtain mechanistic and morphological information that is experimentally challenging to access. The well-known transition from a film with many pinholes, for a low evaporation rate, to a smooth film, for high evaporation rates, is recovered in simulation and experiment. The simulation results provide us with an unprecedented understanding of the crystallization process. They show that supersaturation and crystallization confinement effects determine the final morphology. The ratio of evaporation to crystallization rates turns out to be the key parameter driving the final morphology. Increasing this ratio is a robust design rule for obtaining high-quality films, which we expect to be valid independently of the material type.
CRIS-Team Scopus Importer:2024-11-22

Suppressing Nonradiative Recombination in Lead-Tin Perovskite Solar Cells through Bulk and Surface Passivation to Reduce Open Circuit Voltage Losses - Zhang, Kaicheng; Späth, Andreas; Almora, Osbel; Le Corre, Vincent Marc; Wortmann, Jonas; Zhang, Jiyun; Xie, Zhiqiang; Barabash, Anastasia; Hammer, Maria; Heumüller, Thomas; Min, Jie; Fink, Rainer; et al. (ACS Energy Letters, 2022)
Lead-Tin perovskite solar cells (Pb/Sn PSCs) are limited by the intrinsic instability of Sn(II), which tends to oxidize forming Sn vacancies in perovskite films. Herein, a Lewis base β-guanidinopropionic acid (GUA) and hydrazinium iodide (HAI) are introduced to effectively passivate the perovskite bulk and surface, respectively. The synergistic approach leads to Pb/Sn PSCs with a promising power conversion efficiency of 20.5% owing to the significantly reduced nonradiative recombination and voltage losses. As a result, the VOC × FF product of PSCs is significantly improved, which is among the highest values documented in the literature, being favorable for perovskite-based tandem applications. Additionally, the strategy demonstrated in this work could also improve the stability of PSCs by enhancing the chemical robustness of the perovskite layer. These results emphasize the significance of bulk and surface passivation in the development of efficient and stable PSCs based on Pb/Sn perovskites.
CRIS-Team Scopus Importer:2022-09-30

Toward Understanding Space-Charge Limited Current Measurements on Metal Halide Perovskites - Duijnstee, Elisabeth A; Ball, James M; Le Corre, Vincent Marc; Koster, L Jan Anton; Snaith, Henry J; Lim, Jongchul (ACS Energy Letters, 2020)
Metal halide perovskite semiconductors have sprung to the forefront of research into optoelectronic devices and materials, largely because of their remarkable photovoltaic efficiency records above 25% in single-junction devices and 28% in tandem solar cells, achieved within a decade of research. Despite this rapid progress, ionic conduction within the semiconductor still puzzles the community and can have a significant impact on all metal halide perovskite-based optoelectronic devices because of its influence upon electronic and optoelectronic processes. This phenomenon thus also makes the interpretation of electrical characterization techniques, which probe the fundamental properties of these materials, delicate and complex. For example, space-charge limited current measurements are widely used to probe defect densities and carrier mobilities in perovskites. However, the influence of mobile ions upon these measurements is significant but has yet to be considered. Here we report the effect of mobile ions upon electronic conductivity during space-charge limited current measurements of MAPbBr(3) single crystals and show that conventional interpretations deliver erroneous results. We introduce a pulsed-voltage space-charge limited current procedure to achieve reproducible current-voltage characteristics without hysteresis. From this revised pulsed current-voltage sweep, we elucidate a lower bound trap-density value of 2.8 +/- 1.8 x 10(12) cm(-3) in MAPbBr(3) single crystals. This work will lead to more accurate characterization of halide perovskite semiconductors and ultimately more effective device optimization.

Understanding Causalities in Organic Photovoltaics Device Degradation in a Machine-Learning-Driven High-Throughput Platform - Liu, Chao; Lüer, Larry; Le Corre, Vincent Marc; Forberich, Karen; Weitz, Paul; Heumüller, Thomas; Du, Xiaoyan; Wortmann, Jonas; Zhang, Jiyun; Wagner, Jerrit; Ying, Lei; Hauch, Jens; et al. (Advanced Materials, 2023)
Organic solar cells (OSCs) now approach power conversion efficiencies of 20%. However, in order to enter mass markets, problems in upscaling and operational lifetime have to be solved, both concerning the connection between processing conditions and active layer morphology. Morphological studies supporting the development of structure–process–property relations are time-consuming, complex, and expensive to undergo and for which statistics, needed to assess significance, are difficult to be collected. This work demonstrates that causal relationships between processing conditions, morphology, and stability can be obtained in a high-throughput method by combining low-cost automated experiments with data-driven analysis methods. An automatic spectral modeling feeds parametrized absorption data into a feature selection technique that is combined with Gaussian process regression to quantify deterministic relationships linking morphological features and processing conditions with device functionality. The effect of the active layer thickness and the morphological order is further modeled by drift–diffusion simulations and returns valuable insight into the underlying mechanisms for improving device stability by tuning the microstructure morphology with versatile approaches. Predicting microstructural features as a function of processing parameters is decisive know-how for the large-scale production of OSCs.
CRIS-Team Scopus Importer:2023-04-28
Keywords: device stability; Gaussian process regression (GPR) prediction; linear Pearson correlations; machine learning; organic solar cells

Understanding Dark Current-Voltage Characteristics in Metal-Halide Perovskite Single Crystals - Duijnstee, Elisabeth A; Le Corre, Vincent Marc; Johnston, Michael B.; Koster, L Jan Anton; Lim, Jongchul; Snaith, Henry J. (Physical Review Applied, 2021)
Hybrid halide perovskites have great potential for application in optoelectronic devices. However, an understanding of some basic properties, such as charge-carrier transport, remains inconclusive, mainly due to the mixed ionic and electronic nature of these materials. Here, we perform temperature-dependent pulsed-voltage space-charge-limited current measurements to provide a detailed look into the electronic properties of methylammonium lead tribromide (MAPbBr(3)) and methylammonium lead triiodide (MAPbI(3)) single crystals. We show that the background carrier density in these crystals is orders of magnitude higher than that expected from thermally excited carriers from the valence band. We highlight the complexity of the system via a combination of experiments and drift-diffusion simulations and show that different factors, such as thermal injection from the electrodes, temperature-dependent mobility, and trap and ion density, influence the free-carrier concentration. We experimentally determine effective activation energies for conductivity of (349 +/- 10) meV for MAPbBr3 and (193 +/- 12) meV for MAPbI(3), which includes the sum of all of these factors. We point out that fitting the dark current density-voltage curve with a drift-diffusion model allows for the extraction of intrinsic parameters, such as mobility and trap and ion density. From simulations, we determine a charge-carrier mobility of 12.9 cm(2)/Vs, a trap density of 1.52 x 10(13) cm(-3), and an ion density of 3.19 x 10(12) cm(-3) for MAPbBr(3) single crystals. Insights into charge-carrier transport in metal-halide perovskite single crystals will be beneficial for device optimization in various optoelectronic applications.

Understanding the Limitations of Charge Transporting Layers in Mixed Lead–Tin Halide Perovskite Solar Cells - Zhang, Kaicheng; Forberich, Karen; Lüer, Larry; García Cerrillo, José; Meng, Wei; Du, Xiaoyan; Le Corre, Vincent Marc; Zhao, Yicheng; Niu, Tianqi; Xue, Qifan; Koster, L Jan Anton; Li, Ning; et al. (Advanced Energy and Sustainability Research, 2021)

Universal Current Losses in Perovskite Solar Cells Due to Mobile Ions - Thiesbrummel, Jarla; Le Corre, Vincent Marc; Peña‐Camargo, Francisco; Perdigón-Toro, Lorena; Lang, Felix; Yang, Fengjiu; Grischek, Max; Gutierrez‐Partida, Emilio; Warby, Jonathan; Farrar, Michael D; Mahesh, Suhas; Caprioglio, Pietro; et al. (Advanced Energy Materials, 2021)
Efficient mixed metal lead-tin halide perovskites are essential for the development of all-perovskite tandem solar cells, however they are currently limited by significant short-circuit current losses despite their near optimal bandgap (approximate to 1.25 eV). Herein, the origin of these losses is investigated, using a combination of voltage dependent photoluminescence (PL) timeseries and various charge extraction measurements. It is demonstrated that the Pb/Sn-perovskite devices suffer from a reduction in the charge extraction efficiency within the first few seconds of operation, which leads to a loss in current and lower maximum power output. In addition, the emitted PL from the device rises on the exact same timescales due to the accumulation of electronic charges in the active layer. Using transient charge extraction measurements, it is shown that these observations cannot be explained by doping-induced electronic charges but by the movement of mobile ions toward the perovskite/transport layer interfaces, which inhibits charge extraction due to band flattening. Finally, these findings are generalized to lead-based perovskites, showing that the loss mechanism is universal. This elucidates the negative role mobile ions play in perovskite solar cells and paves a path toward understanding and mitigating a key loss mechanism.
Keywords: current losses; mobile ions; non-radiative recombination; perovskite solar cells; Sn perovskite; transient photoluminescence

Unravelling material properties of halide perovskites by combined microwave photoconductivity and time-resolved photoluminescence spectroscopy - Kupfer, Christian; Le Corre, Vincent Marc; Li, Chaohui; Lüer, Larry; Forberich, Karen; Kato, Masashi; Osvet, Andres; Brabec, Christoph (Journal of Materials Chemistry C, 2024)
To take advantage of the huge compositional space of metal halide perovskites, a reliable and fast characterization method is required. By combining time-resolved photoluminescence (trPL) with microwave photoconductivity measurements, we are able to rapidly extract fundamental material properties of promising perovskite materials from bare films. This is achieved by incorporating a rate-equation model into a fitting algorithm based on Bayesian optimization to globally fit the experimental results. Including microwave photoconductivity measurements into our analysis significantly enhances the accuracy of estimating recombination rate constants. Additionally, it grants us the ability to determine the ratio of electron and hole mobilities, a crucial charge transport property that cannot be obtained solely through time-resolved photoluminescence measurements. Furthermore, the high sensitivity of microwave photoconductivity measurements to long-lived trap states yields information about the trap-assisted recombination, which is a major source of efficiency loss for solar devices and is difficult to assess from pure trPL measurements. In this work, we introduce the fundamental principles of microwave photoconductivity, along with the employed rate-equation model and fitting techniques. We then outline the procedure for conducting measurements and extracting the recombination rate constants, trap density, and mobility ratio. Subsequently, we highlight the benefits of combining both methods through a comparison of results from fits using only trPL with those from fits incorporating combined signals on a simulated dataset. We also discuss the merits of conducting intensity-dependent measurements. Finally, we present the annealing-dependent results obtained from a highly relevant triple-cation, mixed-halide perovskite, FA0.82MA0.13Cs0.05Pb(I0.87Br0.13)3, as an application example, where we uncover the presence of long-lived traps beyond 10 μs.
Created from Fastlane, Scopus look-up

Voltage-Dependent Photoluminescence and How It Correlates with the Fill Factor and Open-Circuit Voltage in Perovskite Solar Cells - Stolterfoht, Martin; Le Corre, Vincent Marc; Feuerstein, Markus; Caprioglio, Pietro; Koster, L Jan Anton; Neher, Dieter (ACS Energy Letters, 2019)
Optimizing the photoluminescence (PL) yield of a solar cell has long been recognized as a key principle to maximize the power conversion efficiency. While PL measurements are routinely applied to perovskite films and solar cells under open circuit conditions (V-OC), it remains unclear how the emission depends on the applied voltage. Here, we performed PL(V) measurements on perovskite cells with different hole transport layer thicknesses and doping concentrations, resulting in remarkably different fill factors (FFs). The results reveal that PL(V) mirrors the current-voltage (JV) characteristics in the power-generating regime, which highlights an interesting correlation between radiative and nonradiative recombination losses. In particular, high FF devices show a rapid quenching of PL(V) from open-circuit to the maximum power point. We conclude that, while the PL has to be maximized at V-OC at lower biases < V-OC the PL must be rapidly quenched as charges need to be extracted prior to recombination.